Clonal Dissemination of Aeromonas hydrophila With Binary Carriage of blaKPC-2-Bearing Plasmids in a Chinese Hospital - Xu, Zhijiang; Shen, Weiyi; Zhang, Rong; Cai, Jiachang (Frontiers in Microbiology, 2022)
Dissemination of Klebsiella pneumoniae carbapenemase (KPC)-encoding gene among Enterobacterales is common but relatively rare in Aeromonas spp. In this study, we characterized two KPC-2-producing Aeromonas hydrophila strains (Ah2101 and Ah2111), each isolated from a patient in different intensive care units of a Chinese hospital. Whole-genome sequencing revealed simultaneous carriage of the blaKPC-2 and imiH gene, both of which encode high-level carbapenem resistance in these two A. hydrophila isolates. The two isolates were shown to be clonally related and each isolate harbored two distinguishable blaKPC-2-bearing plasmids, only one of which was transferrable to A. hydrophila, but not Escherichia coli EC600 via conjugation. The genetic element that contains blaKPC-2 in these two plasmids, namely ISKpn27-ΔblaTEM-1-blaKPC-2-ISKpn6, was structurally identical, commonly detected in Enterobacterales, and associated with Tn3-based transposons. In addition, more than sixty putative genes that encode various virulence factors were identified in these two A. hydrophila isolates. This is the first study that reports clonal dissemination of carbapenem-resistant A. hydrophila strains carrying structurally different blaKPC-2-bearing plasmids. Further investigation is warranted to monitor future transmission of blaKPC-2-bearing plasmids in A. hydrophila in clinical settings.